Eksplorasi Kepuasan Pengguna PayPal Digital Wallet di Indonesia: Pendekatan UTAUT 2 - Laksono, Cindy Fitri; Maulana, Ribas Satria; Wahyuni, Eka Dyar; Wulansari, Anita (LPPM Universitas Sains dan Teknologi Komputer, 2025)
Technological developments and globalization encourage people to develop in the transaction process. Now, conventional technology is starting to be abandoned and switched to a digitalization system, thus strengthening the balance of trade on an international scale. As one of the global e-wallets, PayPal offers convenience in cross-border transactions, but there are not many studies that specifically evaluate the level of satisfaction of Indonesian users in the application of this service. This research focuses on analyzing the level of satisfaction of using PayPal in Indonesia in cross-border transactions and examining technology acceptance factors with the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) method. Data were collected through distributing questionnaires to active PayPal users in Indonesia and analyzed quantitatively using structural regression methods (SEM/PLS). The results showed that perceived ease of use, usefulness, and trust have a significant influence on user satisfaction. In addition, UTAUT 2 variables such as performance expectations, effort expectations, social influence, and hedonic value also contribute to forming positive perceptions of using PayPal. The findings are expected to contribute to the development of an international digital payment system that is more responsive to the needs of users in Indonesia.